The Effect of Adding Various Levels of Crystal Coconut Sugar on Total Solid and Color in Red Dragon Fruit Yoghurt (Hylocereus polyrhizus L) - Syamsul Anwar; Siti Rahmawati Zulaikhah; Arif Harnowo Sidhi (Indonesian Journal of Food Technology, 2022)
The purpose of this study was to determine the effect of adding various levels ofcrystalline coconut sugar to the total solids and color of red dragon fruit yogurt. This study used an experimental method with a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments used in this study were the addition of 0%, 5%, 10% and 15% (w/v) crystal coconut sugar. The variables observed were total dissolved solids and color, which included brightness (L*), greenish-reddish color (a*), and bluish-yellowish color (b*). The results showed that all treatments had an effect on the total dissolved solids and the color of the yogurt produced. The total solids in the addition of 15% crystal coconut sugar had the highest total solids with 18.38°Brix and the lowest was the addition of 0% with 8.02°Brix. The brightness (L*) of Yoghurt color is lowest at the addition of 15% crystal coconut sugar, the addition of crystal coconut sugar shows a greenish-reddish color (a*) will tend to lead to a greenish color, and for a bluish-yellowish color (b*) will tend to lead to a yellowish color.